Role of Variance on Mathematical Expectation - Paeyndah, Azizullah (Journal of Natural Sciences – Kabul University, 2020)
The concept of mathematical expectation originated in connection with games of chance. In its simplest form, mathematical expectation is the product of the amount a player stands to win and the probability of winning. The idea of expected value emerged in the mid-17th century from the study of the so-called "problem of points," which seeks to divide stakes fairly between two players. This problem had been debated for centuries, with many conflicting proposals and solutions suggested over the years. It was posed in 1654 by French writer and amateur mathematician Chevalier de Méré to Blaise Pascal. Méré claimed that the problem could not be solved and that it revealed flaws in mathematics' application to the real world.